Prescription audit of outpatients in tertiary care government hospital - U. S., Nuthan Kumar; G. K., Nalini; P., Deepak; M., Prema; Rathod, Geeta; N., Mohith (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Prescription audit is a tool as well as a technique by its application,all professionals will improve the quality of prescribing drugs. Standards of medical treatment can be assessed by prescription audit. It is based on documented evidences to support diagnosis, treatment and justified utilization of hospital facilities. Prescription audit is a quality improvement process that seeks to improve patient care. In this background the present study was conducted. The objectives of the study were to know the frequently prescribed drugs in OPD, number of the drugs used per prescription and to find out the rationality. Methods: Study was conducted at Sri Chamarajendra Hospital, HIMS, Hassan in OPD of General Medicine.1000 prescriptions were collected and noted down the frequently used medication, number of drugs prescribed and their type of formulations for the particular diagnosis. Results: From the study it is noted that 1910 drugs out of 1000 prescriptions were prescribed which is approximately 1.91 drugs per prescription about 55% of the prescriptions contained single drug. Very few received 4-5 drugs (7%). Almost all the drugs in prescriptions were in Generic names. Around 95% of prescriptions doses were mentioned in mg, ml etc. The most commonly prescribed drugs in order are Antibiotics, antidiabetics antihypertensives, bronchodilators, steroids antiemetics and ORS were prescribed. Conclusions: Polypharmacy was not found in our prescriptions which indicates our prescriptions improved the patient conditions. This type of study will ensure to know the ‘P’ drug development and select the essential medicine list for various levels of health care.